O letramento literário na formação de professores de Ensino Religioso - uma leitura do Mito do Dilúvio em um conto de Machado de Assis - Araceli Sobreira Benevides (Universidade do Estado do Rio Grande do Norte, 2013)
This article takes as theoretical lenses to dialogical conception of language and theories of reading and literary literacy within the context of training teachers of Religious Education. The aim is to bring to the teacher's education field litterary texts whose theme discusses Transcendent and religious phenomenon, in order to create moments of reading to understand the different ways in which religious discourses that are constituted by language. For this, we chose the short story "Na Arca - três capítulos inéditos do Genesis", wroten by Machado de Assis, relating it to the Myth of the Flood, in this sacred narratives to dialogue with the discourses that circulate in the literary's field and epistemological knowledges from Sciences of Religion. The analysis shows how literature can re-upgrade myths to give new interpretations and questions, as does Machado de Assis, the positioning of the characters of the biblical narrative as subjects of everyday life, approaching the characteristics of the more mythical than real. We understand that subsidizes training future teachers of these insights can contribute to more efficient reading practices.